The function of natural compounds in important anticancer mechanisms - Nan, Yang; Su, Hongchan; Zhou, Bo; Liu, Shumin (Frontiers in Oncology, 2023)
The existence of malignant tumors has been a threat to human life, health, and safety. Although the rapid development of radiotherapy, drug therapy, surgery, and local therapy has improved the quality of life of tumor patients, there are still some risks. Natural compounds are widely used in cancer because they are easy to obtain, have a good curative effects and have no obvious side effects, and play a vital role in the prevention and treatment of various cancers. Phenolic, flavonoids, terpenoids, alkaloids, and other natural components of traditional Chinese medicine have certain anti-tumor activities, which can promote apoptosis, anti-proliferation, anti-metastasis, inhibit angiogenesis, change the morphology of cancer cells and regulate immune function, etc., and have positive effects on breast cancer, liver cancer, lung cancer, gastric cancer, rectal cancer and so on. To better understand the effects of natural compounds on cancer, this paper screened out four important pathways closely related to cancer, including cell death and immunogenic cell death, immune cells in the tumor microenvironment, inflammation and related pathways and tumor metastasis, and systematically elaborated the effects of natural compounds on cancer.